APPLICATION OF VIBROWAVE IMPACT (VIBRATIONS) IN DISASSEMBLING FIXED DEMOUNTABLE JOINTS UNDER RESTORATION AND RECLAMATION OF ENGINEERING PRODUCTS - Anatoly P. Babichev; Dieudonné Essola; Ekaterina N. Kovalenko; Nikolay S. Koval; Boris A. Goncharov (Вестник Донского государственного технического университета, 2018)
Some problems on disassembling fixed demountable joints by oscillations forced by the waveguide are considered. The obtained results of the study characterizing the relationship between the used scheme of the vibro-loading, the target exposure period, and the disassembly efficiency are shown.